Morfofunktsional'nye vozmozhnosti zhenshchin v protsesse dolgovremennoi adaptatsii k nagruzkam sovremennogo sporta - Iordanskaya, F. A. (Teorija i Praktika fiziceskoj Kul'tury, 1999)
The aim of this study was to consider the main points of women's adaptation to the extreme training loads in elite sport training. 362 elite female athletes, members of Russian juniors and main national teams in 10 types of sport acted as subjects of this research. The processes of the prolonged adaptation and desadaptation had been investigated. The zones of various orientation in loads were classified. The running, acute and prolonged morphofunctional indices of women's adaptation at the process of physical culture and sports activities were offered. The weak points of adaptation were revealed.